Amnioreduction in cases of polyhydramnios: Indications and outcomes in singleton pregnancies without fetal interventions. (October 2019) - Erfani, Hadi; Diaz-Rodriguez, Gian Esteban; Aalipour, Soroush; Nassr, Ahmed; Rezaei, Atefeh; Gandhi, Manisha; Mendez-Figueroa, Hector; Aagaard, Kjersti M.; Shamshirsaz, Alireza A.
Abstract: Objective: To evaluate indications, pregnancy outcomes, and risk of adverse events following amnioreduction procedures in singleton gestations. Study design: Study of all amnioreduction procedures performed on singleton gestations complicated by polyhydramnios between January 2011 and June 2018 at our tertiary and regional referral fetal center. Clinical indications for amnioreduction procedures were categorized as either maternal shortness of breath, perceived abdominal tightness, or preterm uterine contractions with or without cervical change. Our primary outcome(s) of interest were: preterm premature rupture of membranes (PPROM), placental abruption, chorioamnionitis and/or preterm delivery, each in isolation or as a composite. Results: Among 358 patients who underwent amnioreduction in the study period, 251 arose from cases of twin-twin transfusion syndrome (TTTS) and 74 were singletons undergoing additional fetal intervention procedures. Each of the remaining 33 patients underwent a median number of one [range 1–12] amnioreductions over the antepartum interval, yielding a total of 66 amnioreduction procedures. Among the study cohort, there were no instances of PPROM, placental abruption, chorioamnionitis or preterm delivery within the 12 h following the procedure but 10.6% experienced preterm delivery within 48 h of amnioreduction. Conclusion: Our data suggests that among singleton gestations, there was a low risk for preterm delivery in close proximity to the procedure and none experienced rupture of membranes, placental abruption, sepsis, fetal demise or neonatal death. This data may be used in counseling of potential candidates for amnioreduction with singleton pregnancies and symptomatic polyhydramnios.